2022
DOI: 10.3847/1538-4357/ac590b
|View full text |Cite
|
Sign up to set email alerts
|

Direct First Parker Solar Probe Observation of the Interaction of Two Successive Interplanetary Coronal Mass Ejections in 2020 November

Abstract: We investigate the effects of the evolutionary processes in the internal magnetic structure of two interplanetary coronal mass ejections (ICMEs) detected in situ between 2020 November 29 and December 1 by the Parker Solar Probe (PSP). The sources of the ICMEs were observed remotely at the Sun in EUV and subsequently tracked to their coronal counterparts in white light. This period is of particular interest to the community as it has been identified as the first widespread solar energetic particle event of sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 121 publications
2
16
0
Order By: Relevance
“…The CME event of 2020 Nov. 29 has been widely studied and identified as the largest widespread SEP event of solar cycle 25 and the direct first PSP observation of the interaction of two successive ICMEs (Cohen et al 2021b;Mitchell et al 2021;Kollhoff et al 2021;Lario et al 2021;Mason et al 2021a;Möstl et al 2022;Nieves-Chinchilla et al 2022).…”
Section: Interplanetary Coronal Mass Ejectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CME event of 2020 Nov. 29 has been widely studied and identified as the largest widespread SEP event of solar cycle 25 and the direct first PSP observation of the interaction of two successive ICMEs (Cohen et al 2021b;Mitchell et al 2021;Kollhoff et al 2021;Lario et al 2021;Mason et al 2021a;Möstl et al 2022;Nieves-Chinchilla et al 2022).…”
Section: Interplanetary Coronal Mass Ejectionsmentioning
confidence: 99%
“…The PAD and first-order anisotropies studies at SolO, STEREO-A, and Wind S/C suggest that diffusive propagation processes were involved. Nieves-Chinchilla et al (2022) analyzed multi-S/C observations and included different models and techniques focusing on creating the heliospheric scenario of the CMEs' evolution and propagation and the impact on their internal structure at PSP . The observations of PSP , STEREO-A, and Wind of type II and III radio burst emissions indicate a significant left-handed polarization, which has never been detected in that frequency range.…”
Section: Interplanetary Coronal Mass Ejectionsmentioning
confidence: 99%
“…The remote-sensing and in-situ plasma measurements were used to constrain the parameters of the LFFS model. Using the coronagraphs onboard STA and SOlar and Heliospheric Observatory (SOHO), Nieves-Chinchilla et al (2022) obtained kinematic CME parameters at 0.1 au from the Graduated Cylindrical Shell (GCS; Thernisien et al (2009)) reconstructions for the ENLIL model. We follow these GCS parameters in this work.…”
Section: Model Setupmentioning
confidence: 99%
“…To model the heliospheric context and solar wind transients during the time interval between Flare1 and Flare2, we selected all the CMEs (excluding minor outflows and "jet-like" eruptions, according to the definition of Vourlidas et al, 2013Vourlidas et al, , 2017 observed between 29 November and 7 December 2020 via inspection of SOHO/ LASCO and STEREO/SECCHI data. In addition, Flare1 was preceded by a similarly directed eruption that originated late on 26 November 2020 (e.g., Lario et al, 2021;Nieves-Chinchilla et al, 2022). We also include this event in our investigation, since it likely led to preconditioning of the heliosphere, which may have affected the propagation speed of the CME associated with Flare1 and the transport of associated SEPs.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Both commenced from the same source region, AR 12790, which was still behind the Earth‐facing eastern limb at the time of Flare1, indicating that its “true” X‐ray class might have been even higher than observed. The first of these eruptions has already gained significant attention, since it was associated with the first widespread SEP event of Solar Cycle 25 and with a CME detected in situ by the PSP and STEREO‐A spacecraft (e.g., Cohen et al., 2021; Giacalone et al., 2021; Kollhoff et al., 2021; Kouloumvakos et al., 2022; Lario et al., 2021; Mason et al., 2021; Mitchell et al., 2021; Möstl et al., 2022; Nieves‐Chinchilla et al., 2022). The configurations of planets and spacecraft within the orbit of Mars on the days of the two flares are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%